UNESCO, Adult education and political mobilization - Marcella Milana (Linköping University Electronic Press, 2014)
In this article the author examine the type of mobilization processes that occur via interactions between the UNESCO and other political actors, and how these processes led to the creation of standard-setting and monitoring instruments, like the Belém Framework for Action (UNESCO 2009) and the Global Report on Adult Learning and Education (UIL 2003, 2013). The findings point at three concurrent processes or modes of mobilization in adult education: landmarking, brokering and framing. Landmarking refers to the process of co-constructing a shared past for a broad set of actors with policy will in adult education; Brokering captures the process of supporting the transaction of values, ideas and information to envision a viable future for adult education; finally framing addresses the structuring of information and intentions to produce materials changes at governmental level in the field of adult education. Drawing on different data sources, for each mode the author present and discuss few of its incidences and visible marks.